Prospecting ocean - Hessler, Stefanie 1987- (The MIT Press, 2019)
The oceans are crucial to the planet's well-being. They help regulate the global carbon cycle, support the resilience of ecosystems, and provide livelihoods for communities. The oceans as guardians of planetary health are threatened by many forces, including growing extractivist practices. Through the innovative lens of artistic research, Prospecting Ocean investigates the entanglement of industry, politics, culture, and economics at the frontier of ocean excavation. The result is a richly illustrated study that unites science and art to examine the ecological, cultural, philosophical, and aesthetic reverberations of this current threats to the oceans. Prospecting Oceans takes as its starting point an exhibition by the photographer and filmmaker Armin Linke, which was commissioned by TBA21-Academy, London, and first shown at the Institute of Marine Science (CNR-ISMAR) in Venice. Linke is concerned with making the invisible visible, and here he unmasks the technologies that enable extractions from the ocean, including future seabed mining for minerals and sampling of genetic data. But the book extends far beyond Linke's research, presenting the latest research from a variety of fields and employing art as the place where disciplines can converge. Integrating the work of artists with scientific, theoretical, and philosophical analysis, Prospecting Ocean demonstrates that visual culture offers new and urgent perspectives on ecological crises
Colophon: This book is an expansion of the research for the eponymous exhibition curated by Stefane Hessler at the Institute of Marine Sciences of the National Research Council of Italy (CNR-ISMAR), Venice, May 23-September 30, 2018
Keywords: Wissenschaft; Kunst; Meeresbiologie; Umweltverschmutzung; Meer; Marine ecology; Art and science; Marine ecology / In art; Art